2005
DOI: 10.1111/j.1651-2227.2005.tb03071.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing panorama of cerebral palsy in Sweden. IX. Prevalence and origin in the birth-year period 1995-1998

Abstract: The decreasing trend from the period 1991-1994 continued, both in children born at term and especially in those born preterm. However, the increase in dyskinetic cerebral palsy in children born at term was a matter of concern. In this group, a perinatal hypoxic ischaemic encephalopathy had been present in 71%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
241
6
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(274 citation statements)
references
References 32 publications
18
241
6
7
Order By: Relevance
“…[4,[14][15][16][17] However, a small increase was reported in USA between 1975 and 1991 [18] while in Sweden the monitoring from the 1950s to the 1990s showed an increase in prevalence from the beginning of the 1970s to the mid 1980s followed by a decrease. [19] Also, in Iceland a decrease in prevalence for term babies was observed in 1997-2003 in comparison with [1990][1991][1992][1993][1994][1995][1996]. [20] In 1998, a network of population-based CP registers, Surveillance of Cerebral Palsy in Europe (SCPE), [21] was established.…”
Section: Introductionmentioning
confidence: 99%
“…[4,[14][15][16][17] However, a small increase was reported in USA between 1975 and 1991 [18] while in Sweden the monitoring from the 1950s to the 1990s showed an increase in prevalence from the beginning of the 1970s to the mid 1980s followed by a decrease. [19] Also, in Iceland a decrease in prevalence for term babies was observed in 1997-2003 in comparison with [1990][1991][1992][1993][1994][1995][1996]. [20] In 1998, a network of population-based CP registers, Surveillance of Cerebral Palsy in Europe (SCPE), [21] was established.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most frequent cause of motor disability amongst children in Europe [2]. The prevalence in Europe has been rather stable over the last 30 years and ranges between 1.5 and 3.0 per 1,000 live births [3].…”
Section: Introductionmentioning
confidence: 99%
“…Our study found the commonest presentation of cerebral palsy to be spastic CP found in 90.2% of the sample followed by atonic (3.9%) and ataxic/mixed CP (3.9%).The other Pakistani study carried out by Nazir B et al found 72% of all CP children to be having spastic CP followed by atonic CP (19%) and athetoid CP (6.7%) 6 . Nafi OA, Tosun A, Himmelmann K, Wichers MJ and Winter S also reported commonest presentation of cerebral palsy as spastic type in Jordanian, Turkish, Swedish, Dutch and American population 11,10,5,12,13,14 . Diplegia was the commonest presentation of spastic CP in our study, found in 33.3%.…”
Section: Discussionmentioning
confidence: 99%